Investigasi Proses Kristalisasi Logam Paduan Amorphous Mg58Cu31Gd11 - Andi Idhil Ismail (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2018)
Bulk Metallic Glass (BMG) gains attractions as a candidate for future material in various applications due to its physical and mechanical properties. The fundamental characterization of the crystallization of Mg58Cu31Gd11 has been performed using in-situ synchrotron radiation technique complemented with differential scanning calorimeter (DSC). The glass transition temperature was detected and the occurrence of two step crystallization found during the process. The existence of Mg2Cu and other more complex compound is suggested. Keywords: bulk metallic glass (BMG), synchrotron radiation, crystallization,